Muslim as a condition in handling organ transplant: The juristic views vs. the practice in Malaysia - Basri, Ibrahim; Lazim, Omar; Zulkifli, Mohd (Medwell Journals, 2016)
Organ transplantation is an operation which involves the replacement of defective organs and tissues with healthy ones from donors. The question whether only Muslim surgeon should handle organs transplant has been subjected to a heat debate over times among Muslim scholars. This study seeks to highlight different views posed by Muslim scholars pertaining to the permissibility of organ transplant in Islam and scrutinize the current practice on organ transplant in Malaysia. Based on a comparative analysis, it is concluded that the condition that the expert must be a Muslim is not suitable to be imposed in Malaysia.